CARDIAC CALSEQUESTRIN AS A POSSIBLE TARGET FOR ARRHYTHMIA - Chakravarty, Harapriya; Sharon, Ashoke (Asian Journal of Pharmaceutical and Clinical Research, 2016)
The term arrhythmia encapsulates all the conditions which result in the change in rhythm of the heart. It is classified broadly into two classes; tachycardia, with increased and rhythm of heart and bradycardia, with decreased rhythm of the heart. In most cases, the arrhythmias are not serious and asymptomatic, however, in some cases it leads to heart attack which becomes fatal. The present review focuses on stepwise understanding of functioning of the heart and its excitation-contraction (EC) coupling followed by the mechanism of arrhythmia and the present line of medications. The systematic flow of blood in and out of the cardiac chambers is due to the rhythmic contraction and relaxation of cardiac muscle, i.e. the EC coupling of cardiac myocyte. Any disruption in the ion flow during the EC coupling causes arrhythmia. Ca ions act as the trigger for the excitationcontraction coupling,; therefore, understanding its movement is an essential to understand the rhythm disorders of the heart. Calsequestrin (CASQ) is the most abundant calcium buffering protein present in the sarcoplasmic reticulum of skeletal and cardiac muscles. This review further focuses on CASQ; its structure and functions. Moreover, it describes the association of CASQ with arrhythmia. With the calcium binding the CASQ attains its linear polymeric structure on the neutralization of its highly electronegative surface. The protein binds calcium with high capacity and intermediate affinity which releases and uptakes calcium reversibly during the EC coupling. Mutation in CASQ genes has been associated with catecholaminergic polymorphic ventricular tachycardia, and moreover, there are quite a few molecules which are known to bind to CASQ and bring about changes in ionic buffering properties. Therefore under suitable optimized conditions CASQ could be chosen as a novel target for cardiac arrhythmia. Scrutinizing the scope of CASQ this review presents the first in depth study suggesting cardiac CASQ as a possible target for arrhythmia. 2+ Keywords: Calsequestrin, Arrhythmia, Tachycardia, Bradycardia, Catecholaminergic polymorphic ventricular tachycardia, Excitation-contraction coupling.